School violence and the exercise of teacher authority: a study with adolescents in São Paulo - Gomes, Aline Morais Mizutani; Piccirillo, Debora; Theodoro, Renan; Komatsu, André Vilela (Pro-posições, 2024)
Abstract This article investigated school violence based on a longitudinal survey conducted with adolescents in São Paulo. This is a quantitative research that analyzed the relation between the experience and the practice of violence among adolescents and their perceptions of the school climate and teachers’ authority with a structural equation model. Results showed that school victimization and relational aggression are related and negatively influence the evaluation of the school climate and the legitimacy of teachers. In turn, when teachers exercise their power based on values such as respect and impartiality, there is a positive effect on students’ perceptions, which might be a key to avoiding conflicts. Resumo Este artigo investigou a violência escolar a partir de um survey longitudinal realizado com adolescentes de São Paulo. Trata-se de uma pesquisa quantitativa que analisou a relação entre a experiência e a prática de violências pelos adolescentes e suas percepções sobre o clima escolar e sobre a autoridade dos(as) professores(as) por meio de um modelo de equação estrutural. Os resultados demonstraram que a vitimização escolar e a agressão relacional estão relacionadas entre si e influenciam negativamente a avaliação do clima escolar e da legitimidade dos(as) professores(as). Por sua vez, quando os(as) professores(as) exercem seu poder pautados em valores como respeito e imparcialidade, há um efeito positivo sobre a percepção dos alunos, o que pode ser uma chave para evitar os conflitos.